ATM/RB1 mutations predict shorter overall survival in urothelial cancer - Yin, Ming (Oncotarget, 2018)
BACKGROUND: Mutations of DNA repair genes, e.g. ATM/RB1, are frequently found in urothelial cancer (UC) and have been associated with better response to cisplatin-based chemotherapy. Further external validation of the prognostic value of ATM/RB1 mutations in UC can inform clinical decision making and trial designs. RESULTS: In the discovery dataset, ATM/RB1 mutations were present in 24% of patients and were associated with shorter OS (adjusted HR 2.67, 95% CI, 1.45–4.92, p = 0.002). There was a higher mutation load in patients carrying ATM/RB1 mutations (median mutation load: 6.7 versus 5.5 per Mb, p = 0.072). In the validation dataset, ATM/RB1 mutations were present in 22.2% of patients and were non-significantly associated with shorter OS (adjusted HR 1.87, 95% CI, 0.97–3.59, p = 0.06) and higher mutation load (median mutation load: 8.1 versus 7.2 per Mb, p = 0.126). MATERIALS AND METHODS: Exome sequencing data of 130 bladder UC patients from The Cancer Genome Atlas (TCGA) dataset were analyzed as a discovery cohort to determine the prognostic value of ATM/RB1 mutations. Results were validated in an independent cohort of 81 advanced UC patients. Cox proportional hazard regression analysis was performed to calculate the hazard ratio (HR) and 95% confidence interval (CI) to compare overall survival (OS). CONCLUSIONS: ATM/RB1 mutations may be a biomarker of poor prognosis in unselected UC patients and may correlate with higher mutational load. Further studies are required to determine factors that can further stratify prognosis and evaluate predictive role of ATM/RB1 mutation status to immunotherapy and platinum-based chemotherapy.